Towards patient-specific medializing calcaneal osteotomy for adult flatfoot: a finite element study. Issue 4 (12th March 2018) - Wang, Zhongkui; Kido, Masamitsu; Imai, Kan; Ikoma, Kazuya; Hirai, Shinichi
Abstract: Clinically in medializing calcaneal osteotomy (MCO), foot and ankle surgeons are facing difficulties in choosing appropriate surgical parameters due to the individual differences in deformities among flatfoot patients. Traditional cadaveric studies have provided important information regarding the biomechanical effects of tendons, ligaments, and plantar fascia, but limitations have been reached when dealing with individual differences and tailoring patient-specific surgeries. Therefore, this study aimed at implementing the finite element (FE) method to investigate the effect of different MCO parameters to help foot and ankle surgeons performing patient-specific surgeries. This study constructed FE models of a flatfoot and a healthy foot based on computed tomography (CT) images. After validating the FE models with experimental measurements, differences in plantar stress were compared between two models and a criterion was established for evaluating the performance of surgical simulations. Four MCO parameters were then studied through FE simulations. Results suggested that the transverse angle, β, and translation distance, d, affected surgical performance. Therefore, special attentions may be recommended when choosing these two parameters clinically. However, the sagittal angle, α, and osteotomy position, p, were found to have less effect on the MCO performance.